Documents of the Catholic Monarchs’ Daughters: Maria (First Part) - Ávila Seoane, Nicolás (De Medio Aevo, 2016)
Edition of the documents issued by the infanta Maria, daughter of the CatholicMonarchs, kept in the Arquivo Nacional Torre do Tombo, the Archivo General de Simancas,Real Academia de la Historia, the Biblioteca Nacional and the Archivo Provincial Histórico dela Comunidad de Padres Franciscanos of Zarauz, preceded by their historical, paleographic anddiplomatic analysis.
Keywords: Diplomatics; Catholic Monarchs; Infant Maria; Castile; Portugal